Role of Childhood Trauma in Shaping Adult Emotional and Behavioral Disorders - Manas, Jay (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
Childhood trauma, including physical, emotional or sexual abuse, neglect as well as exposure to domestic violence, has some major effects on the long term functioning in terms of emotion as well as behavior. Premature negative experience interferes with essential neurodevelopmental activities, specifically in the amygdala, hippocampus, and prefrontal cortex, which affect emotional regulation, cognitive ability and executive functions. The dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis also increases the level of stress sensitivity and is a factor leading to persistence of hyperarousal, hypervigilance and maladaptive coping mechanisms, such as substance use, self-harm and social withdrawal. Studies have shown that there is a definite dose-response relationship, the more and worse negative childhood events (ACEs) one has, the more risks they face of psychiatric disorders in adulthood: depression, anxiety, post-traumatic stress disorder (PTSD), personality disorders, and attachment problems. Strong evidence of these associations is presented by longitudinal studies, including the Adverse Childhood Experiences (ACE) Study, cross-sectional surveys, neuroimaging, and qualitative interviews, and they point to both psychological and neurobiological processes. These are emotional dysregulation, cognitive distortions, disrupted attachment, and impaired coping, which are considered to be major determinants of the long-term effects of trauma. Adults who have 4 or higher ACEs have over 2 times more risk of experiencing mental health disorders than persons with no trauma exposure. These data highlight the role of early identification, trauma-informed care, and supportive care giving in reducing the long-term effects of childhood trauma and fostering resilience and enhancing mental health outcomes throughout the lifespan.